A causal-comparative study of South African pre-service primary mathematics teachers' spatial visualization ability: does common content knowledge matter?. Issue 9 (23rd September 2022) - Shongwe, Benjamin
Abstract : This study used a modified mathematical knowledge for teaching (MKT) framework to compare the common content knowledge (CCK) of two groups of purposively selected pre-service primary mathematics teachers ( n = 86) in relation to spatial visualization. Specifically, thirty-five pre-service teachers ( n 1 = 35) with a pure school mathematics background and fifty-one pre-service teachers ( n 2 = 51) with a high school mathematical literacy background worked on problems that involved spatial objects, their properties and relationships. The responses of pre-service teachers with a mathematical literacy content background to the Surface Development Test (SDT) were significantly different from their counterparts' which suggested that their CCK in relation to spatial visualization was thin. Analysis of the Probes questionnaire which inquired about the pre-service teachers' views on the concept of spatial visualization showed that misconceptions hindered their performance. Future research directions are discussed.